TV News: The news’s construction on the syncretic text - Diniz, Maria Lúcia Vissotto Paiva (2008)
The TV News characterizes itself as a syncretic text, set up by a language interaction (gesture, verbal, visual, sounds etc.), that establishes simulacres of the Natural world, because it can’t include it totally. Our semiotic-object are news broadcasted by the TV News programs Jornal Nacional and Jornal da Cultura. We want to investigate how this simulacrum is set. Using the French Semiotics, we are going to study the contents plan, applying the generative process, and some questions of the expression plan (colors, camera’s frame, sonority etc.). We are going to consider the TV News as an informative genre that has the biggest credit and is broadcasted by television, a medium of vast audience. As a ritual, the TV News are on air during the mealtime, so the ethical restrictions with the watchers and the persuasive, esthetic and passional implications that capture our adhesion. Keywords: Enunciation. Syncretism. TV News.